Pengaruh Edukasi Gizi Terhadap Pengetahuan Gizi Pada Remaja Putri Di Kabupaten Maros - Suherman Rate; Syamsopyan Ishak; Ritma Dewanti; Iin Wahyuni (Sekolah Tinggi Ilmu Kesehatan Adila Bandar Lampung, 2023)
Background: Adolescence is a transitional period from childhood and adulthood, which begins with sexual maturity. During this period there is a rapid growth and development of physical, mental, emotional and social. Adolescents are a group that is vulnerable to nutritional problems. Methods: The design of this study used experimental research with pre-test and post-test designs. The sample was 34 class IX students who were selected by cluster random sampling. This research was analyzed by paired test. Nutrition education is given by lecture method using audio-visual (video) and power point slides. Results: there is an effect of nutrition education on nutritional knowledge in female adolescents with p = 0.000. Conclusion: There is an effect of nutrition education on nutritional knowledge in female adolescents.